Inclusion Class Management Model for Children with Special Needs in SLBN Penukal Abab Lematang Ilir District - Nur`aini, Nur`aini; Annur, Saipul; Yuniar, Yuniar (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Education is a right for all Indonesian children without exception, both normal children in general and children who have special needs. Children with special needs need unique methods, materials, services, education, and equipment to achieve optimal development because they may learn at different speeds and in various ways. This study aims to see the classroom management model applied in inclusion classes for children with special needs in Penukal Abab Lematang Ilir District Public Special School. This research is expected to provide a comprehensive picture of the application of the inclusion class management model. Qualitative research with a descriptive design and case study approach was used in this study. Data was collected through interviews, observation, and document analysis. The study subjects involved SLBN Penukal Abab Lematang Ilir district school principals and teachers. Data analysis techniques are done through data reduction, data presentation, and conclusions, providing an in-depth understanding of the inclusion class management model. The inclusion class management model is based on three aspects: physical environment management, socio-emotional condition management, and organizational condition management.Keywords: Classroom Management, Inclusion, Children`s Special Needs.